Effect of increasing levels of soil copper on growth of young rubber (Hevea brasiliensis) plants - M.D. Jessy, P. Prasannakumari (Journal of Plantation Crops, 2017)
Although copper is a micro-nutrient which is essential for the growth of plants, its accumulation in soil can have toxic effects on plant growth. Copper fungicides are regularly used in many rubber plantations for controlling fungal diseases. A study was conducted to assess the copper sensitivity of young rubber plants. Three sets of polybag experiments were conducted in the glass house to study the effect of varying levels of copper in soil on growth of young rubber plants. For experiments 1 and 2, the treatments included 0, 10, 20, 30, 40, 50 and 100 mg Cu per kg soil, incorporated as CuSO4. 5H2O into the soil in the polybag. In the first experiment, treatments of copper were incorporated in the soil used for filling the polybags, before planting budded stumps. In the second experiment, treatment incorporation was carried out in the polybags, at the time of maturity of first whorl of leaves. The third experiment was conducted in soils with inherently low and high copper status, but comparable organic carbon status and pH. Low level of copper (10 mg kg-1 soil) had a positive effect on sprouting, growth and dry matter production of young plants when copper was incorporated in soil before planting budded stumps. This effect was not observed beyond the level of 10 mg Cu kg-1 soil. Beyond 30 mg Cu kg-1 soil, some of the growth parameters, such as height, leaf area and total dry matter were significantly decreased. Copper at a rate of 100 mg kg-1 soil adversely affected growth and dry matter production of plants. Copper content of leaf and stem did not increase with increasing levels of soil copper. However, copper content of root showed significant increase with increasing levels of soil copper. Though excess copper was accumulated in roots, it was not translocated to the shoot, indicating locking up in roots as a tolerance mechanism. Similar results were observed in Experiment 2 also where copper was incorporated at the stage of maturity of first whorl. When plants were grown in soils that were inherently low and high in available copper status, no significant difference in growth of plants was observed, indicating that soil copper content of 20 mg kg-1 does not adversely influence the growth of young plants of Hevea.